Dietary fibre and the occurrence of gut symptoms in cystic fibrosis. Issue 1 (1st January 1997) - Gavin, J; Ellis, J; Dewar, A L; Rolles, C J; Connett, G J
Abstract : OBJECTIVE: To evaluate the effect of currently recommended energy rich cystic fibrosis diets on fibre intake and to investigate the relationship between fibre intake and the occurrence of gut symptoms. METHOD: Prospective completion of non-weighed five day food diaries by 28 children with cystic fibrosis and comparison of mean daily fibre intake with age matched controls who did not have cystic fibrosis. Prospective completion of similar diaries to a total of 68 children with cystic fibrosis and comparison of fibre and lipase intake with the occurrence of gut symptoms. RESULTS: Mean daily fibre intake in children with cystic fibrosis was 7.00 g compared with 14.65 g in controls (p<0.001). Mean daily fibre intake in eight patients troubled with moderate or severe abdominal pain was 0.144 g/kg. This was significantly lower (p<0.01) than mean values for 22 patients with occasional but mild symptoms (0.249 g/kg) and 38 with no gut symptoms (0.312 g/kg). There was a trend towards higher pancreatic enzyme doses (lipase/kg/day) in children with abdominal pain. CONCLUSIONS: Currently recommended cystic fibrosis diets have a low fibre content. A low residue diet might be an important factor in the pathogenesis of gastrointestinal symptoms.